PENGEMBANGAN BAHAN AJAR ELEKTRONIK (BAE) BERBANTUAN FLIPBOOK BERBASIS KETERAMPILAN PEMECAHAN MASALAH DENGAN PENDEKATAN CTL PADA PEMBELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR - Rusnilawati Rusnilawati; Eva Gustiana (Profesi Pendidikan Dasar, 2017)
The aim of this research is to produce Flipbook-based Electronic Teaching Materials based on problem solving skills with CTL Approach in Elementary School Class V that was valid, practical, and effective. The type of research is development research. This research developed Flipbook-assisted Electronic Teaching Materials on the mathematics learning of Class V Elementary School by using the 4-D, the model was developed by Thiagarajan, Semmel, and Semmel. The validation result indicated that The Electronic Teaching Materials developed was feasible to be used with good minimum category. The results of the field trial showed that The Electronic Teaching Material developed was practical and effective. The practicality was assessed by the students and reached 62.5 with good category. The practicality assessed by the teacher reached 25.5 (very good) on material aspect; 13.5 (very good) on the language aspect; and 35 (very good) on aspects of interest and influence. The student's problem solving skill on posttest is 92.9%. There was an increase in scores obtained by the students in steps that were understanding the problem, planning, implementing the plan, and looking back. The percentage of student attitudes toward mathematics with very good category increased 42,8%, the percentage of student attitudes toward mathematics with good category increased 31,25%.